Sistem Pendukung Keputusan untuk Proses Kenaikan Jabatan Pada PT. Suzuki Sejahtera Buana Trada Pekanbaru dengan AHP - Basorudin .; Hendri Maradona (RJOCS (Riau Journal of Computer Science), 2018)
Decision support systems are computer-assisted decision-making processes to assist decision-makers using certain data and models to resolve some unstructured issues. While Analytic Hierarchy Process (AHP) is a method or tool in making decisions that are multi criteria by using Expert Choice software software Ver.11. Criteria used as a benchmark in determining the selection of employees who will rise certain positions on PT.Suzuki Sejahtera Buana Trada namely: skill (Ability), potential, abilities and skills. From this study found that skill is priority or priority on PT.Suzuki Sejahtera Buana Trada and from these three employees Rudi Widodo has a much better skill and meets the criteria for promotion compared to the other 2 employees on behalf of Syamsul and Nanda.